Learning algorithms for packaging design - Божко, Т. О. (Art and Design, 2018)
The purpose of the paper is to consider and select the learning activities algorithms for the process of training the design of packaging products proficients. The article gives a detailed review of the preparatory stages of learning activities for the independent implementation of packaging products projects. The methodology of the research implies using the method of system-comparative analysis and method of comparison of algorithms for professional design and learning design activities. The article proves the irrelevance between students' expectations for insight in setting and solving project tasks. The article determines the necessity for the conscious impression of synthetic and integrated nature of design operation. The article formulates and allocates 6 stages of learning activity, namely: accumulation of experience of the designer in relation to the possibilities of forming the packaging structures and their further transformation, depending on the materials and manufacturing technologies; studying of analogues of packaging products; design problems formulation, according to each project situation; the generation of ideas; the formation of variational project proposals; testing generated offers and choosing the most optimal solution. The originality of the work is to establish the distinct stages of educational designing and to reveal the essential encountered contradictions that should be solved by the designer in the process of mastering the design skills of the packaging products. The practical value of the research is its influence on the process of training graphic designer. This process includes following components: the formation of basic knowledge; development of observation; analysis skills; creative thinking skills and ideas generation; process management modification and the skills of accurate technical reproduction of the specified modification using a wide range of image tools; empathy and skills of reasonable selection of project proposals.